Integrating palliative care into comprehensive cancer management: A systematic review of components and impacts on patient quality of life - Tarigan, Ade Margaretha Lister; Basabih, Masyitoh (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The integration of palliative care into comprehensive cancer management has been shown to confer benefits, yet its influence on patient quality of life remains inconsistently reported across studies. Purpose: To assess the impact of incorporating palliative care components into cancer treatment on patient‑reported quality of life outcomes. Method: A systematic review was conducted in accordance with PRISMA guidelines. Literature searches were performed in PubMed, Scopus, and ProQuest Health and Medicine using keywords related to palliative care, comprehensive cancer treatment, and quality of life. Studies were eligible if they compared patients receiving integrated palliative and oncological care with those receiving standard oncological care with minimal or no palliative involvement. Data extraction and risk of bias assessments were undertaken using standardized protocols. Results: Integration of palliative care was associated with improvements in patient‑reported quality of life, particularly in domains such as pain control, psychosocial well‑being, and communication. Multidisciplinary coordination yielded significant benefits in reducing symptom burden and enhancing emotional support. Conclusion: Incorporating palliative care into cancer treatment enhances patient quality of life. Future investigations should prioritize the development and standardization of intervention protocols to maximize clinical outcomes.